Research and Collaboration on the Efficiency of Financial Management and Zakat Distribution in Malaysia and Indonesia (S/O 13821) - Saad, Ram Al Jaffri; Rajemi, Mohamad Farizal; Abdul Wahab, Muhammad Syahir; Anuar, Herman Shah; Mat Samsudin, Mohd Amir (UUM, 2020)
This study aims to analyse predictors for factors influencing zakah compliance behaviour using attitude towards zakah and intention to pay zakah as independent variables.